Pengaruh Persepsi Layanan dan Promo Harga Maxim terhadap Kepuasan Pelanggan pada Mahasiswa Universitas Islam Negeri Walisongo Semarang - Wanda Ardika; Eko Setyo Nugroho; Nur Fazlin; Khairani Zikrinawati; Zulfa Fahmi (Student Scientific Creativity Journal, 2024)
This study aims to measure the Effect of Service Perceptions and Price Promos on Customer Satisfaction in Walisongo State Islamic University Students in Semarang. The data collection technique used in this study was in the form of a questionnaire in the form of a Google form which was distributed to students of the Walisongo State Islamic University Semarang who use Maxim transportation services with a sample of 100 respondents. Based on the results of the analysis, it can be stated that service perceptions and price promos simultaneously influence customer satisfaction of Maxim service users with an F-count value of 11.933 with sig < 0.001. Perceptions of service and price promos have a partially positive and significant effect on customer satisfaction at UIN Walsiongo Semarang students.